Navigating Negative Events: How Ethical Perceptions Influence Consumer–Company Identification - Ge, Jianxin; Li, Xiaohan; Li, Tong; Lin, Song (Advances in Social Sciences Research Journal, 2025)
This study examines how consumers’ perceptions of the quality of corporate ethics statements influence consumer–company identification (CCI) in the aftermath of negative events.A survey was conducted with 179 consumers of Didi, a prominent Chinese ride-hailing platform that faced public controversy.The findings indicate that the perceived quality of ethics statements positively impacts CCI. Furthermore, collectivism serves as a positive moderator, strengthening the relationship between perceived ethics statement quality and CCI. Conversely, consumer experience acts as a negative moderator, weakening this relationship. This research offers actionable insights for corporate relationship marketing strategies. Companies seeking to enhance consumer identification should prioritize genuine alignment between their actions and ethical statements, underscoring the critical role of corporate ethics in navigating consumer relationships during crises.This study contributes to the literature on corporate social responsibility (CSR) by shedding light on the role of consumers’ perceptions of ethical statements in the context of negative corporate events, with a focus on collectivist cultural settings.